PERBAIKAN KESUBURAN TANAH MELALUI PENGOLAHAN LIMBAH PERTANIAN DI SUBAK TELUN AYAH, BALI - I Nengah Muliarta; Desak Ketut Tristiana Sukmadewi; Dewa Gede Wiryangga Selangga; I Gede Kariasa; Desak Ayu Diah Prawerti; I Komang Adi Parwata; I Wayan Landra (Department of Agricultural Product Technology, Faculty of Agricultural Technology, Universitas Andalas Kampus Limau Manis - Padang, Sumatera Barat Indonesia-25163, 2023)
Limbah pertanian cenderung dipandang sebagai bahan buangan oleh petani, sehingga sering terbuang percuma dan dibakar. Limbah pertanian yang terbuang pada dasarnya merupakan bahan organik yang mengandung unsur hara yang dibutuhkan tanaman. Dampaknya petani membutuhkan jumlah pupuk yang lebih banyak untuk meningkatkan produksi, disisi lain petani membuang bahan baku pupuk yang bermanfaat bagi kesuburan dan kesehatan tanah. Keterbatasan pengetahuan petani mengenai kandungan hara makro dan mikro limbah pertanian menyebabkan limbah dibuang dan dibakar. Umumnya petani juga tidak mengetahui metode pengomposan limbah pertanian, khususnya limbah jerami padi. Kondisi ini juga terjadi di kawasan Subak Telun Ayah, Tegalalang, Gianyar. Guna mengatasi permasalahan petani, maka dilakukan penyuluhan atau sosialisasi terkait kandungan limbah dan upaya pengolahan melalui pengomposan. Petani diberikan pengetahuan terkait pengomposan limbah pertanian dengan cepat, mudah dan menghasilkan kompos berkualitas dengan memanfaatkan dekomposer alami (seperti kotoran hewan dan tanah subur). Petani juga diberikan pengetahuan terkait manfaat dari kompos dari limbah pertanian bagi kesuburan tanah. Harapannya petani memiliki pengetahuan terkait pengelolaan limbah pertanian dan mampu memanfaatkannya, sehingga kedepannya mampun mewujudkan pertanian yang ramah lingkungan. Kata kunci: sosialisasi, limbah pertanian, pengelolaan limbah, kesuburan tanah, Subak ABSTRACT Agricultural waste tends to be seen as a waste material by farmers, so it is often wasted and burned. Agricultural waste that is wasted is basically organic material that contains nutrients needed by plants. As a result, farmers need more fertilizer to increase production, on the other hand, farmers throw away fertilizer raw materials that are beneficial for soil fertility and health. The limited knowledge of farmers regarding the macro and micro nutrient content of agricultural waste causes the waste to be disposed of and burned. Generally, farmers also do not know the method of composting agricultural waste, especially rice straw waste. This condition also occurs in the Subak Telun Ayah area, Tegalalang, Gianyar. In order to overcome farmers' problems, counseling or socialization related to waste content and processing efforts through composting is carried out. Farmers are given knowledge related to composting agricultural waste quickly, easily and to produce quality compost by utilizing natural decomposers (such as animal manure and fertile soil). Farmers are also given knowledge regarding the benefits of compost from agricultural waste for soil fertility. The hope is that farmers have knowledge related to agricultural waste management and are able to use it, so that in the future they are able to realize environmentally friendly agriculture Keywords: socialization, agricultural waste, waste management, soil fertility, Subak